Cinema after the Human: Robotics, AI, and Posthuman Narratives on Screen - El Fahli, Mourad (Interconnections / Interconnexions)

(untitled) (Posthumanism Research Institute, 2026)
This article explores the way in which contemporary film engages posthumanism through robotic, artificial intelligence, and cyborg subjectivities. Drawing on the critical perspectives of Rosi Braidotti, Donna Haraway, and N. Katherine Hayles, the study examines how films such as Ex Machina (2014), and Blade Runner 2049 (2017) interrogate the boundaries of human/non-human existence. Rather than simply representing techno-utopian or dystopian visions, the films stage philosophical and ethical interrogations into consciousness, embodiment, memory, and agency. By rendering non-human viewpoints ontologically prominent and evading anthropocentric assumptions, posthuman cinema both reflects and generates cultural anxieties about technological change, biopolitics, and environmental catastrophe.